PENERAPAN GAME EDUKASI TATA SURYA BERBASIS ANDROID UNTUK SISWA - Gentur Wahyu Nyipto Wibowo; Joko Minardi; Nadia Annisa Maori (ABDI KAMI: Jurnal Pengabdian Kepada Masyarakat, 2023)
In the teaching and learning process, the creativity of the teaching staff is needed, one of the teaching methods is to use learning media. Moreover, it is supported by the development of information technology which is very advanced and rapidly developing as it is today. This community service activity discusses the application of android-based solar system educational games for elementary school students. The purpose of this activity is to introduce an innovative approach to solar system learning that involves technology. This activity includes a description of the development and application of android-based educational games specifically designed for students of SDN 4 Plajan, Jepara Regency. The method of implementing this activity begins with a survey of the needs of the students, activity planning, activity implementation and activity evaluation. The results of this activity open up new opportunities in education by providing learning methods that are interesting, effective, and stimulate student interest in exploring solar system science.